Pair distribution function analysis of the reassembly step of the assembly-disassembly-organisation-reassembly (ADOR) process. Issue 47 (23rd November 2022) - Russell, Samantha E.; Costa, Fanny N.; Diaz-Lopez, Maria; Morris, Russell E.
Abstract : Differences in the ADOR reassembly step were revealed by in situ pair distribution function analysis. Abstract : An in situ pair distribution function study assessing the reassembly of three IM-12 (UTL) intermediate materials to the corresponding fully connected materials. A greater level of atomic change is observed at higher temperatures for the reassembly of the fully disconnected intermediate, IPC-1P, compared to the two partially connected intermediates of IPC-2P and IPC-6P.